PENGARUH MODEL PEMBELAJATAN GUIDED INQUIRY TERHADAP HASIL BELAJAR SISWA KELAS VIII PADA SPLDV DI PONPES AI-YISIFIYAG - Isra Novidayanti Matondang; Yuni Rhamayanti; Puspa Riani Nasution (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2021)
One thing that must be considered in learning mathematics is the model or method used in the learning process, because the method has an important role in determining student success. This study aimed to determine whether there is an effect of student motivation and interest in learning on learning outcomes on the subject of linear equations of one variable. The population in this study were students of class VIII Ponpes Al-Yusufiyah, with the number of class VIII as many as 7 classes. In this study, the sample was taken from the population using the Cluster Random Sampling technique, namely the research took the sample based on a predetermined population area. The number of samples is 20 students. The data collection method used in this study is a questionnaire and documentation method. For the final data analysis using Simple Linear Regression. The constant (a) is 36.714, meaning that if the Guided Effect level variable is 0, then the volume variable for learning outcomes is 36,714. The regression coefficient of the Guided Inquiry variable has a positive value of 13.671 indicating that if the learning outcomes increase by 1 (unit), then the way the learning outcomes increase by 13.671 coefficients is positive, meaning that there is a positive relationship between Guided Inquiry and Learning Outcomes.